2014
DOI: 10.1007/s11665-014-1226-y
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Behavior of 17-4 Precipitation Hardenable Steel Processed by Selective Laser Melting

Abstract: The mechanical behavior and the microstructural evolution of 17-4 precipitation hardenable (PH) stainless steel processed using selective laser melting have been studied. Test coupons were produced from 17-4 PH stainless steel powder in argon and nitrogen atmospheres. Characterization studies were carried out using mechanical testing, optical microscopy, scanning electron microscopy, and x-ray diffraction. The results show that post-process heat treatment is required to obtain typically desired tensile propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(99 citation statements)
references
References 34 publications
(2 reference statements)
6
73
1
1
Order By: Relevance
“…Other steels, e.g., M2 tool steel [96,[129][130][131] and 17-4 PH stainless steel [132][133][134][135][136] have also been reported.…”
Section: Materials Manufactured With Slmmentioning
confidence: 99%
“…Other steels, e.g., M2 tool steel [96,[129][130][131] and 17-4 PH stainless steel [132][133][134][135][136] have also been reported.…”
Section: Materials Manufactured With Slmmentioning
confidence: 99%
“…However, although the mechanical properties have become close to those of bulk materials [3][4][5][6][7][8][9][10][11][12][13][14], SLM has some inherent drawbacks such as warping, cracking and detrimental tensile residual stresses (TRS). A large degree of shrinkage occurs during liquid -solid transformation, thus accumulating considerable tensile residual stresses on the surface of the SLM produced components.…”
Section: Introductionmentioning
confidence: 99%
“…The microstructures of powder-bed AM processed samples can be affected significantly by various factors including beam energy density, beam speed, local heat transfer conditions, and scan strategy. In a study by Reafi et al on AM parts prepared by Selective Laser Melting (SLM) using 17-4 precipitation hardenable (PH) stainless steel, it was reported that a nonequilibrium microstructure developed [1]. This microstructure exhibited a strong difference in texture components parallel and perpendicular to the build direction resulting from the very high cooling rates.…”
mentioning
confidence: 99%